Computer tool to evaluate the cue reactivity of chemically dependent individuals - Silvaa, Meire Luci da [UNESP]; Frere, Annie France; Quintino de Oliveirac, Henrique Jesus; Neto, Helio Martucci; Scardovelli, Terigi Augusto (Elsevier B.V., 2017)
Background and objective: Anxiety is one of the major influences on the dropout of relapse and treatment of substance abuse treatment. Chemically dependent individuals need (CDI) to be aware of their emotional state in situations of risk during their treatment. Many patients do not agree with the diagnosis of the therapist when considering them vulnerable to environmental stimuli related to drugs. This research presents a cue reactivity detection tool based on a device acquiring physiological signals connected to personal computer. Depending on the variations of the emotional state of the drug addict, alteration of the physiological signals will be detected by the computer tool (CT) which will modify the displayed virtual sets without intervention of the therapist. Methods: Developed in 3ds Max (R) software, the CT is composed of scenarios and objects that are in the habit of marijuana and cocaine dependent individual's daily life. The interaction with the environment is accomplished using a Human-Computer Interface (HCI) that converts incoming physiological signals indicating anxiety state into commands that change the scenes. Anxiety was characterized by the average variability from cardiac and respiratory rate of 30 volunteers submitted stress environment situations. To evaluate the effectiveness of cue reactivity a total of 50 volunteers who were marijuana, cocaine or both dependent were accompanied. Results: Prior to CT, the results demonstrated a poor correlation between the therapists' predictions and those of the chemically dependent individuals. After exposure to the CT, there was a significant increase of 73% in awareness of the risks of relapse. Conclusion: We confirmed the hypothesis that the CT, controlled only by physiological signals, increases the perception of vulnerability to risk situations of individuals with dependence on marijuana, cocaine or both. (C) 2016 Elsevier Ireland Ltd. All rights reserved.
Keywords: Computer tool; Anxiety; Cue reactivity; Chemically dependent